PWE-436 Understanding why the at-risk population do not take up colonoscopy following a positive screening test and attendance at nurse (ssp) assessment clinic within the bowel cancer screening programme (bcsp). (22nd June 2015) - Taggart, N; Mbuyongha, M; Fitzgerald, G; Leedham, L; Mumtaz-Wong, S; Davies, D; Lowe, G; Morton, B; Gibson, H; Hymer, W; Sarkar, S
Abstract : Introduction: The success of BCSP is dependent on ensuring that people with positive screening test results (positive FOB) go through for a colonoscopy. Consequently, a QA standard of 90% is set for the conversion rate of attendances of positive assessment (SSP) clinic to colonoscopy. The aim of this study was to understand for why our at-risk population that attended SSP clinic did not progress to colonoscopy. Method: Following identification on BCSS, cases between 2/14 and 11/14 were audited using a standard profoma of attendances to clinic but non-conversion to colonoscopy to ascertain the reasons why. If necessary a follow up phone call by SSP was performed. Results: Of the 532 patients that attended SSP clinic, the conversion rate to colonoscopy was 95%. Only 27 declined colonoscopy (Non-conversion rate 5.1%). The majority were male (n = 21; 78%) who were 2.5 fold more likely not to convert than females (non-conversion rate of 6.6% v 2.8% respectively). Geographically, two thirds of non-converters were from the Wirral, which is a more affluent, high uptake region compared to Liverpool. The non-conversion rate was 2.5 fold greater in the Wirral (7.6%) than in Liverpool (3.1%). The reasons for non-conversion were; personal reasons (22.2%), had a recent colonoscopy, (18.5%), treatment for another cancer (14.8%), wanted to wait for another test kit (11.1%), fear (7.4%), complex co-morbidities (7.4%), under another surveillance programme (3.7%) and travel involved (3.7%). Of total that attended clinic in Wirral only 0.8% found the travel to the Liverpool for colonoscopy an issue. The range of non-conversion amongst individual SSPs was 0–9.1%. Further telephone contact did not change the patient's reasons for going onto colonoscopy. Conclusion: This study confirms that females better embrace screening programmes. The reasons for non-conversion were diverse. Reassuringly a large proportion of reasons were understandable and the distance to travel for colonoscopy did not seem to be an issue. The higher rate of non-conversion in a higher uptake and socio-economic region is difficult explain but now specific health promotion can be targeted around the benefits of colonoscopy in this area. Telephone follow up of non-converters seems to be of no benefit. The overall excellent conversion rate of 95% reflects the high standard of SSP performance within the programme and little conclusion can be drawn from the range of non-conversion between individual SSPs which are likely to reflect statistical bias due to low numbers. Disclosure of interest: None Declared.